The Influence of Pentagon Fraud on Fraudulent Financial Reporting in Companies Registered on the IDX BUMN20 Indonesia Stock Exchange for the 2020-2022 Period - Sagala, Indah Cahya; Sirait, Devi Ayu Putri; Sitorus, Rut Nopiyanti (Information Management and Business Review, 2024)
Financial Statement Fraud is fraud or manipulation of a company’s financial statements to show the best condition of the company so that investors are interested and/or retain the funds owned by the company. This research is intended to analyze the influence of the factors in the fraud Pentagon theory on fraudulent financial reports in companies listed on IDX BUMN20 on the Indonesia Stock Exchange for the 2020-2022 period. The proxy variables used in this research are Pressure proxied by Financial Target and External Pressure, Opportunity proxied by Ineffective Monitoring, Rationalization proxied by Change of Auditor, Competence proxied by Change of Director, and Arrogance proxied by Frequent Number of CEO’s Picture and Fraudulent financial reporting measured by F-Score. The data used in this research is secondary data obtained from the annual reports of companies listed on IDX BUMN20 on the Indonesia Stock Exchange for the 2020-2022 period. The number of samples used was 18 samples from companies selected through the purposive sampling technique. The data analysis used in this research is logistic regression analysis. The research results show that the partial test results do not influence each of the independent variables, namely financial target, external pressure, ineffective morning, change of auditor, change of directors, and frequent number of CEO’s pictures on fraudulent financial reporting, but the simultaneous test results show that there is an influence the entire independent variable to the dependent variable is fraudulent financial reporting.